Percepción estética de los componentes de la sonrisa según Roy Sabri en estudiantes de la facultad de odontología, Universidad Nacional De La Amazonía Peruana, 2023 - Mathews Saldaña, Renzo Daniel (2023)
The aim of the report was to know the aesthetic perception of the components of the smile according to Roy Sabri in students of the Faculty of Dentistry, National University of the Peruvian Amazon 2023. Working under a quantitative study, non-experimental design and descriptive level, taking as a population 355 students taking a sample of 185, to whom a registration form was used to collect information. The results showed, the perception of the aesthetics of the lip line, the average smile is perceived as pleasant; while the non-consonant smile arc is perceived as unpleasant; the curved smile of the straight upper lip is perceived as pleasant; Likewise, the smile with medium negative spaces is considered pleasant; The aesthetic perception of the symmetrical smile is considered as pleasing; The aesthetics of the smile with a straight anterior occlusal plane is perceived as pleasing; On the other hand, the smile with a midline is perceived as pleasant; Finally, the smile with curvature of the lower gingival margin is perceived as unpleasant.